Nanoparticles of tungsten as low-cost monometallic catalyst for selective hydrogenation of 3-hexyne - Maccarrone, María Juliana (2016)
Low-cost tungsten monometallic catalysts containing variable amounts of metal (4.5, 7.1 and 8.5%W) were prepared by impregnating alumina with ammonium metatungstate as an inexpensive precursor. The catalysts were characterized using ICP, XPS, XRD, TPR and hydrogen chemisorption. These techniques revealed mainly WO3-Al2O3 (W6+) species on the surface. The effects of the content of W nanoparticles and reaction temperature on activity and selectivity for the partial hydrogenation of 3-hexyne, a non-terminal alkyne, were assessed under moderate conditions of temperature and pressure. The monometallic catalysts prepared were found to be active and stereoselective for the production of (Z )-3-hexene, had the following order: 7.1WN/A > 8.5 WN/A ≥ 4.5 WN/A. Additionally, the performance of the synthesized xWN/A catalysts exhibited high sensitivity to temperature variation. In all cases, the maximum 3-hexyne total conversion and selectivity was achieved at 323 K. The performance of the catalysts was considered to be a consequence of two phenomena: a) the electronic effects, related to the high charge of W (+6), causing an intensive dipole moment in the hydrogen molecule (van der Waals forces) and leading to heterolytic bond rupture; the H+ and H- species generated approach a 3-hexyne adsorbate molecule and cause heterolytic rupture of the C≡C bond into C- = C+; and b) steric effects related to the high concentration of WO3 on 8.5WN/A that block the Al2O3 support. Catalyst deactivation was detected, starting at about 50 min of reaction time. Electrodeficient W6+ species are responsible for the formation of green oil at the surface level, blocking pores and active sites of the catalyst, particularly at low reaction temperatures (293 and 303 K). The resulting best catalyst, 7.1WN/A, has low fabrication cost and high selectivity for (Z )-3-hexene (94%) at 323 K. This selectivity is comparable to that of the classical and more expensive industrial Lindlar catalyst (5 wt% Pd). The alumina supported tungsten catalysts are low-cost potential replacements for the Lindlar industrial catalyst. These catalysts could also be used for preparing bimetallic W-Pd catalysts for selective hydrogenation of terminal and non-terminal alkynes.